Protective Framework of Law for the Unaccompanied Migrant Children (UMC) in the UK: Plights and Proposals - Kabir, Ahmed Ehsanul Kabir; Chowdhury, Shuvra (Dhaka University Law Journal, 2026)
Unaccompanied children are separated from their parents and relatives at the time of applying for asylum in the UK, and the immigration authority recognises them as unaccompanied migrant children (UMC). The main responsibility to look after the rights and interests of the UMC has been conferred upon the local authorities in the UK by the Children Act (CA), 1989. However, the protective framework of law has also been suffering from many flaws that undermine the rights and interests of the UMC. Such flaws include the exclusion from the care leaver support, less access, and barriers to educational facilities and health care support. The UK government has enacted some legislation consistent with the hostile environment policy with a view to curtailing and shrinking the rights of the UMC. This article tries to identify the precarious and uncertain conditions of the UMC in the UK and provides how to safeguard the welfare and well-being of the UMC within the protective framework of law in the era of hostility and austerity. Dhaka University Law Journal, 2025, 36(2), 141-160